Cytotoxicity, antimicrobial and antioxidant activities of Boletus bicolor, A basidiomycetes mushroom indigenous to Tanzania - Tibuhwa, Donatha (Tanzania Journal of Science, 2017)
Boletus bicolor commonly known as coloured bolete is a basidiomyctes mushroom species widely used as a delicacy and its extract has been used traditionally to treat several human ailments in Tanzania. This study evaluates its extracts in order to provide a scientific foundation on the possible application in folk medicine system based on the biochemical evaluation. Standard microbes Bacillus subtilis and Candida albicans were used to test, the antifungal and antibacterial activity. Cytotoxicity test was also done on the extracts using brine shrimp test. Besides, the extracts were also used to investigate for antioxidant activity using DPPH (1, 1-diphenyl-2-picrylhydrazyl radical). Quantitative analyses for ß-carotene, lycopene, total phenolic compounds and vitamin C contents were also determined using spectrophotometric assay at 515 nm. The study result revealed B. bicolor methanol extracts to exhibit positive antimicrobial activity against Bacillus subtilis forming an inhibition zone of up to 2.3 mm/2days while it had no effect on Candida albicans. It further portrayed relatively mild cytotoxic activity with the LC50 value of 113.75μg/ml. The phenolic compounds were recorded high up to 187.45 GAE mg/g, ß-carotene 15.7 mg/g, Lycopene 23.81 mg/g and Vitamin C content 5.09 mg/100g. Likewise the radical scavenging ability was also high and concentration dependent with maximum ability at 1 ml/100g and EC50 value of 0.046 mg/ml. The findings from this study supports the traditional medicinal use of this mushroom and envisage a purposeful thoroughly study for isolating the bioactive compounds, up-scaling and possible developments into nutraceutics. Keywords: mushroom, Boletus, antimicrobial antifungal, inhibition, cytotoxicity, basidiomycetes